Evaluation of antimicrobial activity of extracts of medicinal plants on three tomato phytopathogens - De Morais, L. A S [UNESP]; Do Carmo, M. G F; Viegas, E. C.; Teixeira, D. F.; Barreto, A. S.; Pizarro, A. P B; Gilbert, B. (My University, 2002)
Antimicrobial activity of 45 extracts of medicinal plants were tested on Xanthomonas campestris pv. vesicatoria, Ralstonia solanacearum and Clavibacter michiganense subsp. michiganense. Some assays were done to verify the capability of these plants extrats to show an antibiosis. Five extracts (EAFQ, SM1, SM12, SM16, SA1) shown positive activity. The extract EAFQ expressed bactericide activity on C. michiganense. It suggests the possibility of using these actives substances in natura or as a model to synthesize industrialized products, intendind field utilization.
Keywords: Antimicrobial activity; Clavibacter michiganense subsp. michiganense; Quassia amara; Ralstonia solanacearum; Spondias mombim; Stryphnodendron adstringens; Xanthomonas campestris pv. vesicatoria